Use of non-pharmacological interventions for comforting patients in palliative care - Coelho, Adriana (2020)
Palliative care aims to provide the maximum possible comfort to people with advanced and incurable diseases. The use of non-pharmacological interventions to promote comfort in palliative care settings has been increasing.However, information on implemented and evaluated interventions, their characteristics, contexts of application, and population is scattered in the literature, hampering the formulation of accurate questions on the effectiveness of those interventions and, consequently, the development of a systematic review.